The Influence of Promotions on Purchase Decision Through Brand Image as a Mediation Variable: Study at The Semprit RIHO Cake Factory - Sari, Diyana Permata; Usdek, Dicky Wisnu; Putri, Viajeng Purnama (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This study aims to determine the effect of promotion on purchasing decisions through brand image as a mediating variable. The sampling technique uses accidental sampling. This research was conducted on consumers of the Semprit factory "RIHO" with a total of 100 respondents. Collecting data in this study using a questionnaire. The data analysis techniques used are path analysis, hypothesis testing using the t-test, and Hayes analysis. The results of this research show that promotion has a positive effect on brand image, brand image has a positive effect on purchasing decisions, promotion affects purchasing decisions and brand image can mediate the effect of promotion on purchasing decisions.